بتلءِ جوڑشتءِ بن دپتر ءُ روایت : History and tradition of proverb - Dashti, Zahid Hussain; Zahid, Durdana (Hanken, 2018)
It is a recognized fact that the proverbs are generally the quintessence of peoples’ collective wisdom. A proverb is a simple and concrete saying, popularly known and repeated, that expresses the truth based on common sense or experience. Proverbs fall into the category of formulaic language and form a folklore genre. However; almost every culture is the examples of its own unique proverb.